ILMU PENDIDIKAN ISLAM TEORITIS DAN PRAKTIS DI ERA GLOBALISASI - Hubbil Khair (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
The Theoretical and practical of Islamic educational in the globalization era must be able to adjust with the current times and the technology development. It must be done in the school, family environment and in the society are to develop Islamic education system with global insight in order to generate good, smart, and innovative human to face global competition. Islamic educationalthat in modernizing atmosphere, nowadays is required to be able to play its role dynamically and proactively. Its presence is expected to bring change for the improvement of the Islamic poeples on the theoretical and practical level. Then what should be done is to develop a system of Islamic education with a global insight.